Memoria del Ateneo Español de México / José María Espinasa ; prólogos de Carmen Tagüeą y Carmen Romero del Rayo - Tagüeą, CarmenRomero del Rayo, Carmen; Espinasa, José María
En la portada: Gobierno de España, Ministerio de la Presidencia